2007
DOI: 10.1016/s0257-5655(07)70004-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Knee Sleeve on Static and Dynamic Balance in Patients with Knee Osteoarthritis

Abstract: Patients with knee osteoarthritis (OA) find that use of elastic knee sleeves gives them partial pain relief and a greater sense of joint stability. However, the scientific effects of knee OA patients wearing braces are unclear. The purpose of this study was to investigate the effects of knee sleeves on static and dynamic balance in knee OA patients. Fifty patients with knee OA were enrolled in the study and all subjects were randomly divided into two groups. Initially, subjects in group A did not wear a neopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 24 publications
3
37
0
15
Order By: Relevance
“…These contribute to pain, changes in muscle control and may interfere with balance and postural control [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…These contribute to pain, changes in muscle control and may interfere with balance and postural control [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…Após cinco minutos, eram realizadas três repetições de cada teste. O intervalo de repouso era de um minuto entre as tentativas, considerando-se o valor médio 14,15 .…”
Section: Resultsunclassified
“…Varus malalignment of the knee has been implicated as a contributing factor to knee OA progression [22], and valgus unloading knee braces may reduce medial knee loading in varus deformity, and improve pain and function [23]. Stability and balance are of particular importance in elderly patients at greater risk for falls, and unloading braces can stabilize the joint and improve balance [24]. However, a systematic review of available studies in 2006, consisting of only two small observational studies, suggested that these braces have limited efficacy in knee OA [25,26].…”
Section: Knee Bracing (Conservative Realignment)mentioning
confidence: 99%